Biometric and morphological features of Dimorphandra mollis Benth. fruits and seeds from the Cerrado of Minas Gerais - Ariane da Silva Nogueira; Leonardo Máximo Silva; Fernanda de Souza Santos; Leovandes Soares da Silva; Nilza Lima Pereira Sales; Ernane Ronie Martins (Ambiente)
The fava-d'anta (Dimorphandra mollis Benth.) is a native species of the Brazilian Cerrado, valued for its economic and ecological importance, especially for its medicinal properties. This study investigated the biometry and morphology of D. mollis fruits and seeds collected in different localities of the Cerrado of Minas Gerais. Fruits and seeds were collected in four localities and submitted to biometric and morphological analyses. Significant variation was observed among localities for traits such as fruit weight, weight of one thousand seeds, number of seeds per fruit and morphological characteristics. Through the dendrogram of dissimilarity, similarities between the populations of the different localities were indicated. The results highlight the importance of locality in the selection of matrices in the determination of the desired characteristics for different uses of D. mollis fruits and seeds.